Fatores nutricionais e antinutricionais no processamento de feijão comum armazenado - Mariotto, Thais Cesar (2011)
The common bean (Phaseolus vulgaris L.) is one of the most important elements of the diet of the Brazilian population, being an excellent source of protein, having good content of carbohydrates and being rich in iron. In addition to providing essential nutrients, it is used as an alternative to meat or other protein products for the population with a low-income. The aim of this study was to assess the influence of storage on the nutrient and antinutritional factors that the beans undergo during their process of cooking. Beans of the Carioca variety IAPAR 81 were assessed at 0, 45, 90, 135 and 180 days of storage and three processes of cooking: baked beans without soaking water (FCSAM), baked beans with soaking water (FCCAM) and baked beans without soaking (FCSM) and raw bean (control). Each sample was analyzed for physical-chemical moisture, total solids, protein, phytic acid, tannin and minerals (calcium, iron and manganese), which were compared to results from raw beans within five days of storage. The results were subjected to analysis of variance (ANOVA) and differences between means were analyzed by Tukey test at 5% probability (p <0.05). It was found that there was significant increase in the cooking time of the stored grain, which indicated hardening of the grain stored at room temperature. Moisture content showed a lower result within 45 days of storage. There was less concentration of protein in beans cooked without soaking water. When analyzing the protein as a function of storage time, it was observed that the beans with 45 days of storage had the highest protein content. By analyzing the content of phytates, it was found that the months of storage decrease the phytate content of the grain, and the best treatment to reduce phytate would be baked beans without soaking water. Since the tannin content showed an increase with storage, and the period of 180 days had the highest concentration of tannins in the grain, its best treatment was the FCSAM. The content of tanning increased in the broth with FCSAM. The storage time was a major factor and influenced the content of protein, phytates, tannins and calcium, reducing or increasing their values as a function of time.